A SCR denitration catalyst and its preparation method and application
By combining phosphate CEO2-AL2O3/W+NI composite powder and amino-based titanium porous microspheres to solve the problem of poor dispersability and lack of abrasion resistance of the cymbal dehydration, it has achieved efficient denitration and long. Life catalyst.
Patent Information
- Application Number
- CN202411388421.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing cerium-based denitrification catalysts have poor dispersion on the support and insufficient catalyst strength and wear resistance, resulting in low denitrification efficiency and short service life.
The combination of phosphate modified CEO2-AL2O3/W+Ni composite powder and amino-based titanium porous porous microspheres to fully disperse the composite powder through static electricity and rejection, and improve the strength and abrasion resistance of the catalyst.
Improve the denitration efficiency and abrasion resistance of the catalyst, extend the service life, and maintain stable performance in a high temperature and corrosive environment.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to an SCR denitration catalyst and a preparation method and application thereof, belonging to the technical field of flue gas treatment. Background Art
[0002] In the field of flue gas SCR denitrification technology, cerium-based denitrification catalysts have attracted extensive attention due to their good low-temperature denitrification performance. However, in practical applications, existing cerium-based denitrification catalysts face a series of challenges, especially the easy agglomeration of cerium dioxide on the carrier, poor dispersion, and poor catalyst strength and wear resistance, which directly affect the denitrification efficiency and service life.
[0003] During the preparation of cerium-based denitrification catalysts, due to the interaction between cerium dioxide particles, agglomerates are easily formed, resulting in poor dispersion on the carrier. This agglomeration phenomenon reduces the number of active sites on the catalyst surface, thereby reducing the denitrification efficiency of the catalyst.
[0004] During operation, denitration catalysts need to withstand complex environments such as high temperature, high dust and corrosive substances in flue gas. However, due to the limitations of the material itself, existing cerium-based denitration catalysts often have problems with poor strength and wear resistance. Poor strength and wear resistance can cause the catalyst to break, wear and even fall off during operation. This not only reduces the denitration efficiency of the catalyst, but also increases operating costs and maintenance difficulties.
[0005] In summary, existing cerium-based denitration catalysts have significant problems in the dispersibility of cerium dioxide and the strength and wear resistance of the catalyst. These problems not only limit the denitration efficiency of the catalyst, but also increase the challenges in its practical application. Therefore, developing new cerium-based denitration catalysts, improving the dispersibility of cerium dioxide, and increasing the strength and wear resistance of the catalyst are important research directions in the current field of flue gas denitration technology. Summary of the invention
[0006] The object of the present invention is to provide an SCR denitration catalyst, a preparation method and an application thereof, in which the phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder can be fully dispersed on the amino-modified titanium niobium oxide porous microspheres, thereby improving the denitration efficiency while improving the overall strength and wear resistance of the catalyst.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing an SCR denitration catalyst comprises the following steps:
[0009] S1, mixing titanium dioxide and niobium pentoxide, and subjecting the mixture to ball milling, drying and calcining to obtain porous titanium niobium oxide microspheres;
[0010] S2, mixing the titanium niobium oxide porous microspheres with ammonia water, heating and stirring, and then centrifuging and drying to obtain amino-modified titanium niobium oxide porous microspheres;
[0011] S3, mixing aluminum nitrate, cerium nitrate and anhydrous ethanol and stirring, and adding tungsten powder and nickel powder during the stirring process to obtain a mixed solution; then adding PEG and ammonia water to the mixed solution, stirring thoroughly, filtering, drying, ball milling, and sintering under an inert atmosphere to obtain CeO2-Al2O3 / W+Ni composite powder;
[0012] S4, dispersing the CeO2-Al2O3 / W+Ni composite powder in a phosphoric acid solution, heating and stirring, centrifuging, washing, and drying to obtain phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder;
[0013] S5. Dispersing amino-modified titanium niobium oxide porous microspheres in an alcohol solution to prepare a suspension; then adding phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder to the suspension, stirring ultrasonically, centrifuging, washing, drying, and calcining to obtain the SCR denitration catalyst.
[0014] Preferably, in step S1, the molar ratio of titanium in titanium dioxide to niobium in niobium pentoxide is 1:2;
[0015] The conditions for ball milling are: 500-800 rpm, 6-10 h;
[0016] Drying conditions: 60-80℃, 2-5h;
[0017] The calcination conditions are: 800-1200°C, 15-25h.
[0018] Preferably, in step S2, the ratio of the porous titanium niobium oxide microspheres to the ammonia water is (1-5) g: (20-30) mL;
[0019] The conditions for heating and stirring are: 60-90°C, 300-500rpm, 3-8h;
[0020] The drying conditions are: 50-70℃, 1-3h.
[0021] Preferably, in step S3, the ratio of aluminum nitrate, cerium nitrate, anhydrous ethanol, tungsten powder and nickel powder is: (1-3) g: (5-10) g: (30-50) mL: (2-5) g: (2-4) g;
[0022] The amount of PEG added is 6-12% of the total mass of aluminum nitrate, cerium nitrate, tungsten powder and nickel powder;
[0023] The amount of ammonia water added is such that the pH of the mixed solution is between 7.5 and 8.5.
[0024] Preferably, in step S3, the drying conditions are: 70-90°C, 3-5h;
[0025] The ball milling conditions were: 300-500 rpm, 8-12 h;
[0026] The sintering conditions are: heating to 450-600°C at a heating rate of 3-5°C / min, and keeping warm for 1-2h; then heating to 1000-1300°C at a heating rate of 7-10°C / min, and keeping warm for 3-7h.
[0027] Preferably, in step S4, the concentration of phosphoric acid in the phosphoric acid solution is 3-5 mol / L, and the ratio of CeO2-Al2O3 / W+Ni composite powder to phosphoric acid solution is (2-7) g: (30-60) mL.
[0028] Preferably, in step S4, the conditions for heating and stirring are: 50-70°C, 150-300rpm, 1-3h;
[0029] Drying conditions are: 60-90℃, 2-5h.
[0030] Preferably, in step S5, the mass ratio of the phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder to the amino-modified titanium niobium oxide porous microspheres is: (1-3): (7-9);
[0031] Drying conditions: 50-80℃, 2-3h;
[0032] The calcination conditions are: 500-700°C, 2-5h.
[0033] An SCR denitration catalyst is prepared by any of the above methods.
[0034] Application of the SCR denitration catalyst prepared by any of the above methods in flue gas denitration.
[0035] The beneficial effects of the present invention are:
[0036] 1. First, PEG is used to increase the dispersion of cerium and aluminum precipitates in the mixed solution after adding ammonia water, and then the sintered CeO2-Al2O3 / W+Ni composite powder is modified with phosphoric acid, and then the amino-modified titanium niobium oxide porous microspheres and the phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powders are combined in an alcohol solution. At this time, the phosphate group will dissociate hydrogen ions to make the surface of the composite powder negatively charged, and the amino group will be protonated to make the surface of the porous microspheres positively charged. Then, the electrostatic effect between positive and negative charges and the repulsion between the same charges can be used to fully disperse the phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder onto the amino-modified titanium niobium oxide porous microspheres. On the one hand, it can reduce the problem of a reduction in the number of catalyst active sites caused by agglomeration, and on the other hand, it can improve the accessibility of the catalyst active sites, and then improve the subsequent denitrification efficiency;
[0037] 2. Alumina, tungsten and nickel as hard phases, after being dispersed on the porous microspheres with the composite powder, can bear part of the load and reduce stress concentration, thereby improving the strength of the material. At the same time, the presence of the hard phase can also resist cutting and scratching during wear, and the interface effect can also hinder the expansion of cracks and improve the wear resistance of the material; the alumina, tungsten and nickel partially dispersed in the porous microspheres can also form a dispersion-strengthened structure, which can hinder dislocation movement and interface slip, thereby improving the strength of the material;
[0038] 3. Alumina, tungsten and nickel all have high thermal stability. Their addition can improve the stability of titanium niobium oxide porous microspheres at high temperatures, so that the resulting catalyst can maintain better performance at a better temperature; at the same time, nickel powder has good corrosion resistance and can also improve the stability of the catalyst in a corrosive environment. DETAILED DESCRIPTION
[0039] The present invention will be specifically described below in conjunction with the embodiments.
[0040] Example 1: This example provides a method for preparing an SCR denitration catalyst, comprising the following steps:
[0041] (1) 10 g of titanium dioxide and 66.25 g of niobium pentoxide were mixed and added to a ball mill, and then 100 mL of n-hexane was poured in, and the mixture was ball milled at 600 rpm for 8 h, and then dried at 60° C. for 3 h, and then calcined at 1000° C. for 20 h, and then ground and sieved to obtain porous titanium niobium oxide microspheres. 30 g of porous titanium niobium oxide microspheres were mixed with 150 mL of ammonia water, stirred at 70° C. and 300 rpm for 3 h, centrifuged, dried at 50° C. for 1 h, and then ground and sieved to obtain amino-modified porous titanium niobium oxide microspheres.
[0042] (2) 20 g of aluminum nitrate, 100 g of cerium nitrate and 500 mL of anhydrous ethanol were mixed and stirred at 300 rpm. During the stirring process, 50 g of tungsten powder and 40 g of nickel powder were added to obtain a mixed solution. 15 g of PEG (polyethylene glycol) was added to the mixed solution and ammonia water was added dropwise until the pH of the mixed solution was 8. After stirring for 1 hour, the mixture was filtered and dried at 80°C for 3 hours and ball-milled at 500 rpm for 8 hours. After ball-milling, the mixture was heated to 500°C at a heating rate of 5°C / min under an inert atmosphere and then kept warm for 2 hours. Then, the mixture was heated to 1100°C at a heating rate of 10°C / min and kept warm for 5 hours to obtain CeO2-Al2O3 / W+Ni composite powder. 30 g of CeO2-Al2O3 / W+Ni composite powder was dispersed in 300 mL of 5 mol / L phosphoric acid solution, stirred at 50°C and 300 rpm for 2 h, washed with deionized water after centrifugation, dried at 70°C for 3 h, and then ground and sieved to obtain phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder.
[0043] (3) Dispersing 21 g of amino-modified titanium niobium oxide porous microspheres in 100 mL of anhydrous ethanol to prepare a suspension; then adding 3 g of phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder to the suspension, stirring ultrasonically for 1 h and then centrifuging, then washing with deionized water, and then drying at 60°C for 2 h, and then calcining at 600°C for 3 h and then grinding and sieving to obtain an SCR denitrification catalyst.
[0044] Comparative Example 1: The preparation method of the SCR denitration catalyst is basically the same as that of Example 1, except that, in Comparative Example 1, after the CeO2-Al2O3 / W+Ni composite powder is obtained, the CeO2-Al2O3 / W+Ni composite powder is not modified with phosphoric acid.
[0045] The specific preparation steps are as follows:
[0046] (1) 10 g of titanium dioxide and 66.25 g of niobium pentoxide were mixed and added to a ball mill, and then 100 mL of n-hexane was poured in, and the mixture was ball milled at 600 rpm for 8 h, and then dried at 60° C. for 3 h, and then calcined at 1000° C. for 20 h, and then ground and sieved to obtain porous titanium niobium oxide microspheres. 30 g of porous titanium niobium oxide microspheres were mixed with 150 mL of ammonia water, stirred at 70° C. and 300 rpm for 3 h, centrifuged, dried at 50° C. for 1 h, and then ground and sieved to obtain amino-modified porous titanium niobium oxide microspheres.
[0047] (2) 20 g of aluminum nitrate, 100 g of cerium nitrate and 500 mL of anhydrous ethanol were mixed and stirred at 300 rpm. During the stirring process, 50 g of tungsten powder and 40 g of nickel powder were added to obtain a mixed solution. 15 g of PEG was added to the mixed solution and ammonia water was added dropwise until the pH of the mixed solution was 8. After stirring for 1 hour, the mixture was filtered and dried at 80°C for 3 hours and ball-milled at 500 rpm for 8 hours. After ball-milling, the mixture was heated to 500°C at a heating rate of 5°C / min under an inert atmosphere and then kept warm for 2 hours. The mixture was then heated to 1100°C at a heating rate of 10°C / min and kept warm for 5 hours. The mixture was then ground and sieved to obtain CeO2-Al2O3 / W+Ni composite powder.
[0048] (3) 21 g of amino-modified titanium niobium oxide porous microspheres were dispersed in 100 mL of anhydrous ethanol to prepare a suspension; 3 g of CeO2-Al2O3 / W+Ni composite powder was added to the suspension, ultrasonically stirred for 1 h, and then centrifuged. The suspension was washed with deionized water, dried at 60°C for 2 h, and calcined at 600°C for 3 h to obtain an SCR deNOx catalyst.
[0049] Comparative Example 2: The preparation method of the SCR denitration catalyst is basically the same as that of Example 1, except that in Comparative Example 2, PEG is not added when preparing the CeO2-Al2O3 / W+Ni composite powder.
[0050] The specific preparation steps are as follows:
[0051] (1) 10 g of titanium dioxide and 66.25 g of niobium pentoxide were mixed and added to a ball mill, and then 100 mL of n-hexane was poured in, and the mixture was ball milled at 600 rpm for 8 h, and then dried at 60° C. for 3 h, and then calcined at 1000° C. for 20 h, and then ground and sieved to obtain porous titanium niobium oxide microspheres. 30 g of porous titanium niobium oxide microspheres were mixed with 150 mL of ammonia water, stirred at 70° C. and 300 rpm for 3 h, centrifuged, dried at 50° C. for 1 h, and then ground and sieved to obtain amino-modified porous titanium niobium oxide microspheres.
[0052] (2) 20 g of aluminum nitrate, 100 g of cerium nitrate and 500 mL of anhydrous ethanol were mixed and stirred at 300 rpm. During the stirring process, 50 g of tungsten powder and 40 g of nickel powder were added to obtain a mixed solution. Ammonia water was then added dropwise to the mixed solution until the pH value of the mixed solution was 8. After stirring for 1 hour, the mixture was filtered and dried at 80°C for 3 hours and ball-milled at 500 rpm for 8 hours. After ball-milling, the mixture was heated to 500°C at a heating rate of 5°C / min under an inert atmosphere and then kept warm for 2 hours. Then, the mixture was heated to 1100°C at a heating rate of 10°C / min and kept warm for 5 hours to obtain CeO2-Al2O3 / W+Ni composite powder. 30 g of CeO2-Al2O3 / W+Ni composite powder was dispersed in 300 mL of 5 mol / L phosphoric acid solution, stirred at 50°C and 300 rpm for 2 h, washed with deionized water after centrifugation, dried at 70°C for 3 h, and then ground and sieved to obtain phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder.
[0053] (3) Dispersing 21 g of amino-modified titanium niobium oxide porous microspheres in 100 mL of anhydrous ethanol to prepare a suspension; then adding 3 g of phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder to the suspension, stirring ultrasonically for 1 h and then centrifuging, then washing with deionized water, and then drying at 60°C for 2 h, and then calcining at 600°C for 3 h and then grinding and sieving to obtain an SCR denitrification catalyst.
[0054] Comparative Example 3: The preparation method of the SCR denitration catalyst is basically the same as that of Example 1, except that in Comparative Example 3, CeO2 is directly prepared using cerium nitrate (this process does not require the additional addition of PEG), and then CeO2 is modified with phosphoric acid and then composited with amino-modified titanium niobium oxide porous microspheres.
[0055] The specific preparation steps are as follows:
[0056] (1) 10 g of titanium dioxide and 66.25 g of niobium pentoxide were mixed and added to a ball mill, and then 100 mL of n-hexane was poured in, and the mixture was ball milled at 600 rpm for 8 h, and then dried at 60° C. for 3 h, and then calcined at 1000° C. for 20 h, and then ground and sieved to obtain porous titanium niobium oxide microspheres. 30 g of porous titanium niobium oxide microspheres were mixed with 150 mL of ammonia water, stirred at 70° C. and 300 rpm for 3 h, centrifuged, dried at 50° C. for 1 h, and then ground and sieved to obtain amino-modified porous titanium niobium oxide microspheres.
[0057] (2) 100g of cerium nitrate was mixed with 500mL of anhydrous ethanol and stirred at 300rpm. Ammonia water was then added to the solution until the pH of the mixed solution was 8. After stirring for 1h, the mixture was filtered and dried at 80℃ for 3h. The mixture was ball milled at 500rpm for 8h. After ball milling, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 2h in an inert atmosphere. The mixture was then heated to 1100℃ at a heating rate of 10℃ / min and kept warm for 5h to obtain CeO2 powder. 30g of CeO2 powder was dispersed in 300mL of 5mol / L phosphoric acid solution and stirred at 50℃ and 300rpm for 2h. The mixture was centrifuged and washed with deionized water. The mixture was dried at 70℃ for 3h and then ground and sieved to obtain phosphoric acid-modified CeO2.
[0058] (3) 21 g of amino-modified titanium niobium oxide porous microspheres were dispersed in 100 mL of anhydrous ethanol to prepare a suspension; 1 g of phosphoric acid-modified CeO2 powder was added to the suspension, ultrasonically stirred for 1 h, centrifuged, washed with deionized water, dried at 60°C for 2 h, calcined at 600°C for 3 h, and then ground and sieved to obtain an SCR denitrification catalyst.
[0059] Catalytic activity test of catalyst: Use simulated flue gas to test the denitrification of catalyst. The simulated flue gas composition is: NO: 500ppm, NH3: 500ppm, O2: 5%, N2 as balance gas, and the air velocity is 30000h -1 , the flue gas flow rate is 300mL / min, and the same volume of catalyst is put into the fixed bed reactor for testing. The denitrification efficiency of the catalyst at different temperatures is tested, and the reaction temperature is controlled at 150~350℃.
[0060] Catalyst anti-water and sulfur stability test: Use simulated flue gas to test the catalyst denitrification situation. The simulated flue gas composition is: NO: 500ppm, NH3: 500ppm, O2: 5%, H2O: 3%, SO2: 100ppm, N2 is the balance gas, and the air velocity is 30000h -1 , the flue gas flow rate is 300mL / min, and the same volume of catalyst is put into the fixed bed reactor for testing. The denitrification efficiency of the catalyst at different temperatures is tested, and the reaction temperature is controlled at 150~300℃.
[0061] A flue gas analyzer was used to detect the NO concentration at the reactor inlet and outlet.
[0062] The calculation formula for denitrification efficiency is:
[0063] Among them, C in is the NO concentration (ppm) at the inlet of the fixed bed reactor. out is the NO concentration at the outlet of the fixed bed reactor (ppm, after 10 hours of testing).
[0064] The SCR denitration catalysts prepared in Example 1 and Comparative Examples 1, 2 and 3 were subjected to the above-mentioned catalyst denitration performance test and water-sulfur resistance stability test, and the performance data shown in Table 1 and Table 2 were obtained respectively.
[0065] Table 1: Denitration efficiency of SCR denitration catalysts prepared in Example 1 and Comparative Examples 1, 2, and 3 at different temperatures
[0066]
[0067] It can be seen from the data in Table 1 that the catalyst prepared by adding PEG and phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder and amino-modified titanium niobium oxide porous microspheres has the best low-temperature denitrification efficiency. The reason is that the addition of PEG can improve the dispersion of cerium and aluminum precipitates generated after the addition of ammonia water in the system, thereby improving the dispersion of CeO2 and Al2O3 in the composite powder, which is beneficial to the subsequent phosphoric acid modification and the exposure of active sites; and when the phosphoric acid-modified composite powder is composited with the porous microspheres, the amino group is protonated to make the surface of the porous microspheres carry positive charges, which will produce electrostatic attraction with the negative charges on the surface of the composite powder, and the negatively charged composite powders will also produce repulsion, thereby making the phosphoric acid-modified composite powder fully dispersed on the amino-modified titanium niobium oxide porous microspheres, reducing the problem of a reduction in the number of catalyst active sites due to agglomeration, and improving the accessibility of the catalyst active sites, thereby improving the denitrification efficiency.
[0068] Table 2: Denitration efficiency of the SCR denitration catalysts prepared in Example 1 and Comparative Examples 1, 2, and 3 at different temperatures after passing water sulfur
[0069]
[0070] It can be seen from the data in Table 2 that the catalyst prepared by the preparation method provided in Example 1 also has excellent water-sulfur resistance.
[0071] Catalyst wear rate test: According to the test method for the wear rate of honeycomb flue gas denitrification catalyst (GB / T31587-2015), the gas flow rate in the catalyst channel is 14.5m / s (standard state), and the concentration of the abrasive (dry 0.300-0.425mm high hardness quartz sand) is 50g / m 3 , flushing time 2h.
[0072] The SCR denitration catalysts prepared in Example 1 and Comparative Examples 1, 2 and 3 were respectively tested for the above-mentioned catalyst wear rate. The results are shown in Table 3.
[0073] Table 3: Wear rate of SCR denitration catalysts prepared in Example 1 and Comparative Examples 1, 2, and 3 after denitration performance test
[0074]
[0075] It can be seen from the data in Table 3 that the wear rate of the denitration catalyst (Example 1, Comparative Examples 1 and 2) doped with aluminum oxide, tungsten and nickel is lower than the wear rate of the denitration catalyst (Comparative Example 3) not doped with aluminum oxide, tungsten and nickel. The reason is that the addition of aluminum oxide, tungsten and nickel exists as a hard phase on the one hand, and also forms a dispersion-strengthened structure on the other hand. As a hard phase, after the composite powder and the porous microsphere are combined, it plays a role in bearing part of the load and reducing stress concentration, and the dispersion-strengthened structure can hinder dislocation movement and interface slip, thereby improving the strength of the material; after the strength is improved, the material can resist cutting and scratching during the wear process, and the interface effect formed after the assembly can also hinder the expansion of cracks and improve the wear resistance of the material. The reason why the wear rate of the denitration catalyst obtained by the preparation method in Comparative Example 1 is better than the wear rate of the denitration catalyst obtained by the preparation method in Example 1 is that in the absence of electrostatic effect and repulsion of the same charge, the composite powder containing the main strengthening effect component is more loaded on the surface of the porous microsphere, thereby reducing the wear rate of the catalyst.
[0076] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a SCR denitration catalyst, characterized in that: The steps include: S1, mixing titanium dioxide and niobium pentoxide, and subjecting the mixture to ball milling, drying and calcining to obtain porous titanium niobium oxide microspheres; S2, mixing the titanium niobium oxide porous microspheres with ammonia water, heating and stirring, and then centrifuging and drying to obtain amino-modified titanium niobium oxide porous microspheres; S3, mixing aluminum nitrate, cerium nitrate and anhydrous ethanol and stirring, and adding tungsten powder and nickel powder during the stirring process to obtain a mixed solution; then adding PEG and ammonia water to the mixed solution, stirring thoroughly, filtering, drying, ball milling, and sintering under an inert atmosphere to obtain CeO2-Al2O3 / W+Ni composite powder; S4, dispersing the CeO2-Al2O3 / W+Ni composite powder in a phosphoric acid solution, heating and stirring, centrifuging, washing, and drying to obtain phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder; S5. Dispersing amino-modified titanium niobium oxide porous microspheres in an alcohol solution to prepare a suspension; then adding phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder to the suspension, stirring ultrasonically, centrifuging, washing, drying, and calcining to obtain the SCR denitration catalyst.
2. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S1, the molar ratio of titanium in titanium dioxide to niobium in niobium pentoxide is 1:2; The conditions for ball milling are: 500-800 rpm, 6-10 h; Drying conditions: 60-80℃, 2-5h; The calcination conditions are: 800-1200°C, 15-25h.
3. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S2, the ratio of the porous titanium niobium oxide microspheres to the ammonia water is (1-5) g: (20-30) mL; The conditions for heating and stirring are: 60-90°C, 300-500rpm, 3-8h; The drying conditions are: 50-70℃, 1-3h.
4. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S3, the ratio of aluminum nitrate, cerium nitrate, anhydrous ethanol, tungsten powder and nickel powder is: (1-3) g: (5-10) g: (30-50) mL: (2-5) g: (2-4) g; The amount of PEG added is 6-12% of the total mass of aluminum nitrate, cerium nitrate, tungsten powder and nickel powder; The amount of ammonia water added is such that the pH of the mixed solution is between 7.5 and 8.
5.
5. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S3, the drying conditions are: 70-90°C, 3-5h; The conditions for ball milling are: 300-500 rpm, 8-12 h; The sintering conditions are: heating to 450-600°C at a heating rate of 3-5°C / min, and keeping warm for 1-2h; then heating to 1000-1300°C at a heating rate of 7-10°C / min, and keeping warm for 3-7h.
6. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S4, the concentration of phosphoric acid in the phosphoric acid solution is 3-5 mol / L, and the ratio of CeO2-Al2O3 / W+Ni composite powder to the phosphoric acid solution is (2-7) g: (30-60) mL.
7. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S4, the heating and stirring conditions are: 50-70°C, 150-300rpm, 1-3h; Drying conditions are: 60-90℃, 2-5h.
8. The method for preparing the SCR denitration catalyst according to claim 1, characterized in that: In step S5, the mass ratio of phosphoric acid-modified CeO2-Al2O3 / W+Ni composite powder to amino-modified titanium niobium oxide porous microspheres is: (1-3): (7-9); the drying conditions are: 50-80°C, 2-3h; The calcination conditions are: 500-700°C, 2-5h.
9. An SCR denitration catalyst, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the SCR denitration catalyst prepared by the method according to any one of claims 1 to 8 in flue gas denitration.
Citation Information
Patent Citations
Selective reduction reaction low-temperature denitration catalyst using catalysis wastes, and preparation method thereof
CN107149941A
SCR (Selective Catalytic Reduction) denitration catalyst for synergistically removing dioxin and preparation method thereof
CN116747874A